Poverty Reduction and Growth Trust : Review of Interest Rate Structure. (Policy Papers; Policy Paper ;, 2014)
This paper provides the basis for the second review of the interest rate structure approved under the 2009 reforms of the Fund's concessional lending facilities. Based on the application of the Poverty Reduction and Growth Trust (PRGT) interest rate mechanism, PRGT interest rates for 2015-16 would be zero percent for both the Extended Credit Facility (ECF) and Rapid Credit Facility (RCF), and 0.25 percent for the Stand-by Credit Facility (SCF). The interest rate on remaining balances of the Exogenous Shock Facility (ESF) is not set by the PRGT interest mechanism and it would be 0.25 percent. In accordance with the PRGT Instrument, the next review of PRGT interest rates will take place by December 31, 2016.